Attitudes towards the use of nicotine products among vocational school students in Finland - Vaihekoski, Anu; Eloranta, Sini; Salakari, Minna; Sillanmäki, Lauri; Lagström, Hanna (Springer Science and Business Media LLC, 2025)
Background
Young people’s use of nicotine products is a global challenge, and it is changing over time. Young people in Finnish vocational education smoke cigarettes more often and rate their health more poorly than other upper-secondary students. The data for this study was collected in November 2020. The study aimed to investigate behaviours, attitudes and opinions about nicotine products among 15–28-year-old Finnish vocational students.
Methods
An electronic questionnaire survey was distributed to and collected from 449 students. The survey data was analysed with SPSS which categorised the participants into nicotine product non-users and users. A factor analysis was done, and the result was a six-factor model with six themes.
Results
Non-users and users had similar attitudes and impressions towards nicotine product. However, non-users disagreed more with the theme “social norms and feelings of pleasure from nicotine products” than the users (p < 0.001). The non-users disagreed more often with the theme of the nicotine appearance of nicotine products than the users did (p < 0.001). As regards the theme “use of nicotine products impacts appearance” the users strongly disagreed more often with this theme than non-users (p < 0.001). Most participants in both groups considered non-smoking fashionable.
Conclusion
Our findings suggest that understanding young people’s behaviour and attitudes towards nicotine products is important for protecting young people’s health. The connections between young people’s attitudes, their use or non-use of nicotine products, and everyday life trends are complex and time-bound. More research using multiple methods is needed to clarify the phenomenon.